Geolocation dengan Metode Djikstra untuk Menentukan Jalur Terpendek Lokasi Peribadatan - Azizah, noor; Mahendra, Danang (Universitas Diponegoro, 2017)
Traveling from one place to another takes time and cost. Especially for tourists who get difficulties to find worship locations because of a vast area with the numbers of worship location. This study aims to design application based android to determine the location of worship with the shortest path. A method used to develop the application is Waterfall method that includes the beginning of the analysis phase up to the application maintenance stage. Result from this research is Djikstra method can searching the location with the shortest path. Geolocation technology is used to identify a real-world geographical location that can be applied to the android operating system. As a case study, this research has been successfully applied to searching the location of worship in Kudus District include mosques, christian churches, catholic churches, and monasteries.